(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to evaluate the association between overweight-obesity and insulin resistance in non-diabetic patients with acute coronary syndrome. Methods: A cross-sectional study was conducted in 126 non-diabetic patients with acute coronary syndrome treated at the University Medical Center Ho Chi Minh City from June 2024 to April 2025. Insulin resistance was assessed using the HOMA2-IR index, with a cut-off value of ≥ 1.35. Overweight-obesity was defined based on BMI, using a cut-off of ≥ 23 kg/m² according to recommendations for Asian populations. Clinical and biochemical variables were analyzed for their associations with HOMA2-IR. Results: Among 126 non-diabetic patients with acute coronary syndrome, the prevalence of overweight and obesity (BMI ≥ 23 kg/m²) was 44.4%. Patients with BMI ≥ 23 kg/m² exhibited significantly higher insulin levels and HOMA2-IR values, along with lower insulin sensitivity (HOMA2-%S), and more pronounced dyslipidemia. BMI was positively correlated with HOMA2-IR (r = 0.36; p < 0.001) and inversely correlated with HOMA2-%S (r = -0.34; p < 0.001). In multivariable regression analysis, BMI ≥ 23 kg/m² remained independently associated with increased HOMA2-IR (β = 0.79; p = 0.012). Conclusion: In non-diabetic patients with metabolic syndrome, overweight and obesity (BMI ≥ 23 kg/m²) were independently and positively associated with insulin resistance as assessed by the HOMA2-IR. These findings highlight the role of excess body weight in early metabolic disturbances and suggest that greater attention to weight assessment and management may contribute to improving prognosis in this patient population.